The Cambridge companion to C.S. Lewis - MacSwain, Robert; Ward, Michael, 1968- (Cambridge ; New York : Cambridge University Press, 2010)
A distinguished academic, influential Christian apologist, and best-selling author of children's literature, C. S. Lewis is a controversial and enigmatic figure who continues to fascinate, fifty years after his death. This Companion is a comprehensive single-volume study written by an international team of scholars to survey Lewis's career as a literary historian, popular theologian, and creative writer. Twenty-one expert voices from Oxford, Cambridge, Princeton, and Wheaton, among many other places of learning, analyze Lewis's work from theological, philosophical, and literary perspectives. Some chapters consider his professional contribution to fields such as critical theory and intellectual history, while others assess his views on issues including moral knowledge, gender, prayer, war, love, suffering, and Scripture. The final chapters investigate his work as a writer of fiction and poetry. This Companion shows that C. S. Lewis was much more than merely the man behind Narnia.
C.S. Lewis: chronology -- Introduction / Robert MacSwain -- Scholar. -- Literary critic / John V. Fleming -- Literary theorist / Stephen Logan -- Intellectual historian / Dennis Danielson -- Classicist / Mark Edwards -- Thinker. -- On scripture / Kevin J. Vanhoozer -- On theology / Paul S. Fiddes -- On naturalism / Charles Taliaferro -- On moral knowledge / Gilbert Meilaender -- On discernment / Joseph P. Cassidy -- On love / Caroline J. Simon -- On gender / Ann Loades -- On power / Judith Wolfe -- On violence / Stanley Hauerwas -- On suffering / Michael Ward -- Writer. -- The Pilgrim's Regress and Surprised by Joy / David Jasper -- The Ransom trilogy / T.A. Shippey -- The Great Divorce / Jerry L. Walls -- The Chronicles of Narnia / Alan Jacobs -- Till We Have Faces / Peter J. Schakel -- Poet / Malcolm Guite.
Includes bibliographical references (p. 311-318) and index.
Keywords: Lewis, C. S. -- 1898-1963.; Literary historians -- Great Britain -- Biography; Theologians -- Great Britain -- Biography; Authors, English -- 20th century -- Biography; Lewis, C. S. -- 1898-1963.